Identifikasi Hubungan Antara Salinitas dan EC (Electrical Conductivity) Untuk Pengembangan Mitigasi Pengukuran Numerik-in Situ di Area Estuari: Mitigasi Kebencanaan Kualitas Air di Muara Kerandangan - Budianto, Arif; Alaydrus, Alfina Taurida; Rahayu, Susi; Andini, Mira; Anggriani, Ni Ketut; Fajarica, Shinta Desiyana (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The dynamic nature of estuarine waters necessitates new and accurate methodological approaches for determining salt content or salinity. This can be achieved through direct and real-time measurement of instantaneous and daily EC (Electrical Conductivity) levels in estuaries using EC sensors. On the other hand, similar real-time research has been limited, especially for studies of a continuous real-time nature. Therefore, this study aims to identify the relationship between EC and salinity in an estuary, using the area around the Batulayar estuary, West Lombok Regency, as a case study, employing a direct measurement model continuously for one full day. Measurements were conducted over 5 days during different lunar phases, using direct data acquisition and a numerical linearity approach via data analysis plug-ins. The identification results demonstrate a relationship between EC and salinity. At minimum values, salinity decreases as EC decreases. This reduction follows a quadratic pattern, with an obtained coefficient of determination (R²) of 0.8684 (y = 87397x² – 11173x + 2004.8). This characteristic is also supported by other measured parameters, such as TDS (Total Dissolved Solids), which exhibits a linear relationship with EC. The relationship characteristic between TDS and EC is considerably stronger, as indicated by a linear equation (R² > 0.90).